تصور الطلبة والأساتذة المتخصصين باللغة العربية وآدابها من الجامعة الإسلامية العالمية بماليزيا في قراءة النصوص العربية المتوفرة في موقع “learning.aljazeera.net” = The perception of IIUM students and lecturers specializing in Arabic language and literature in reading the Arabic texts on the “learning.aljazeera.net” website - Muhd Suffian, Nur Auni Faqihah; Abu Bakar, Radhwa (Usuli Faqih Research Centre, 2024)
قراءة النصوص العربية أمر أساسي في إتقان اللغة، خاصة للطلبة المتخصصين في اللغة العربية. ومع ذلك، لا يزال بعض الطلبة يواجهون صعوبات في قراءة النصوص العربية ويخطئون عند القراءة. غالبا ما يتعرض الطلبة لمواد مطبوعة معقدة. وهكذا، تم تطوير العديد من المواقع الإلكترونية لتعلم اللغة العربية خلال العقد الماضي، ويُنظر إلى موقع “learning.aljazeera.net” هذا على أنه مصدر محتمل لممارسة قراءة النصوص العربية. يركز هذا المقال بشكل خاص على تصور الطلبة والأساتذة المتخصصين باللغة العربية وآدابها من الجامعة الإسلامية العالمية بماليزيا في قراءة النصوص العربية المتوفرة في موقع “learning.aljazeera.net”. تهدف هذه الدراسة إلى تسليط الضوء على تصورات الطلبة والأساتذة تجاه قراءة النصوص العربية في الموقع. تستخدم الدراسة المنهج الوصفي التحليلي لكشف ميزات الموقع، والمنهج النوعي لجمع تصورات الطلبة والأساتذة قراءة النصوص العربية في الموقع. وفقًا لنتائج هذه الدراسة، يحتوي هذا الموقع على مميزات مثيرة للاهتمام يمكن أن تلفت الانتباه وتساعد الطلبة في قراءة النصوص العربية. يعتقد معظم الطلبة والأساتذة أنه أمر ممتع ومفيد. على الرغم من أنه تعليم إلكتروني، إلا أن بعض الطلبة والأساتذة يعتقدون أن قراءة النصوص العربية هنا تتطلب مساعدة أساتذة أو خبراء. ***** Reading Arabic text is essential to mastering the language, especially for students specialising in Arabic. However, some students still struggle to read Arabic texts and make mistakes when reading. Students are also frequently exposed to complex printed materials. Thus, many websites for learning Arabic have been developed over the past decade, and this learning.aljazeera.net website is seen as a potential source to practice reading the Arabic texts. In particular, this article focuses on the perceptions of International Islamic University Malaysia (IIUM) students and lecturers specialising in Arabic language when reading Arabic texts on the “learningaljazeera.net” website. This study aims to investigate the students' and lecturers' perceptions of reading the Arabic text on this website. The study uses the descriptive analytics method to analyse the features of the website and the qualitative method to collect the perceptions of students and lecturers on reading the Arabic text on this website. According to the findings of this study, this website contains intriguing elements that can draw attention and assist students in reading Arabic texts. Most students and teachers think that it is interesting and beneficial. Despite the fact that it is e-learning, some of the students and lecturers believe that reading the Arabic texts here requires the assistance of a teacher or an experienced person.